2000
DOI: 10.1080/15298660008984520
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Fluoride as an Exposure Index in Aluminum Smelting

Abstract: Urinary fluoride was evaluated as an exposure index for a prospective study of asthma in an aluminum smelter. Two studies were conducted to evaluate the relationship between airborne exposure and urinary excretion over a workweek, and to describe exposures among jobs and over time. Thirty-two subjects were evaluated on Days 1 and 3 of a 3-day workweek. On each day, spot urine samples were collected prior to the start of work and again at the end of the shift. Samples were analyzed for fluoride and expressed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
2
7
1
1
Order By: Relevance
“…56 Different studies have shown that the aluminum industry discharges fluoride into the air, and several studies have shown a slight but significant contribution to the intake of fluoride by children living around aluminum smelters. 30,31 The research 30 found that fluoride excretion decreases with age in children (r = 0.31), but the authors do not discuss any interfering factors, for example, dental treatment with fluorine-containing drugs or the use of bottled water with fluorine. In a different country, total fluoride intake, urinary excretion, and consequently fluoride retention no longer reflect residence in a community with a nonfluoridated or fluoridated water supply 67,68 because of fluoride toothpaste of 57%, 35%, and 47% for children receiving low, suboptimally, and optimally fluoridated water, respectively.…”
Section: Fluorine (F) Contamination Of Urban Child Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Different studies have shown that the aluminum industry discharges fluoride into the air, and several studies have shown a slight but significant contribution to the intake of fluoride by children living around aluminum smelters. 30,31 The research 30 found that fluoride excretion decreases with age in children (r = 0.31), but the authors do not discuss any interfering factors, for example, dental treatment with fluorine-containing drugs or the use of bottled water with fluorine. In a different country, total fluoride intake, urinary excretion, and consequently fluoride retention no longer reflect residence in a community with a nonfluoridated or fluoridated water supply 67,68 because of fluoride toothpaste of 57%, 35%, and 47% for children receiving low, suboptimally, and optimally fluoridated water, respectively.…”
Section: Fluorine (F) Contamination Of Urban Child Populationsmentioning
confidence: 99%
“…28 Rare articles have reviewed potential health hazards that may also pose health risks 29 to some communities because of their proximity to aluminum smelters. 21,30,31 They pinpoint that there is a potential for materials such as sulfur dioxide, particulate matter, fluorides, and beryllium capable of posing health risks to communities. 21 Its toxic action is insignificant; however, many water-soluble inorganic compounds, as well as its satellite elements F, Be, and Li, are long-preserved and Chemical Contamination of Soil on Urban Territories With Aluminum Production in the Baikal Region, Russia Numerator-minimum-maximum; denominator-average.…”
Section: Introductionmentioning
confidence: 99%
“…The entity is referred to as "Potroom asthma" [73,[190][191][192][193][194]. Suspicious etiologic factors are particulates of aluminum sodium fluoride along with hydrogen fluoride and other gases [194][195][196][197][198][199].…”
Section: Irritant-assumed Conditionsmentioning
confidence: 99%
“…Post-shift urinary fluoride is considered as an appropriate index for surveillance of exposure to fluoride in aluminum smelter [9]. On the other hand, according to Aylward et al [10], urinary flow and creatinine excretion are strongly individual and may vary from person to person.…”
Section: Introductionmentioning
confidence: 99%